Transcriptome Analysis of Hypothalamic Gene Expression during Daily Torpor in Djungarian Hamsters (Phodopus sungorus) - Cubuk, Ceyda; Kemmling, Julia; Fabrizius, Andrej; Herwig, Annika (Frontiers in Neuroscience, 2017)
Animals living at high or temperate latitudes are challenged by extensive changes in environmental conditions over seasons. Djungarian hamsters (Phodopus sungorus) are able to cope with extremely cold ambient temperatures and food scarcity in winter by expressing spontaneous daily torpor. Daily torpor is a circadian controlled voluntary reduction of metabolism that can reduce energy expenditure by up to 65% when used frequently. In the past decades it has become more and more apparent, that the hypothalamus is likely to play a key role in regulating induction and maintenance of daily torpor, but the molecular signals, which lead to the initiation of daily torpor, are still unknown. Here we present the first transcriptomic study of hypothalamic gene expression patterns in Djungarian hamsters during torpor entrance. Based on Illumina sequencing we were able to identify a total number of 284 differentially expressed genes, whereby 181 genes were up- and 103 genes downregulated during torpor entrance. The 20 most up regulated group contained eight genes coding for structure proteins, including five collagen genes, dnha2 and myo15a, as well as the procoagulation factor vwf. In a proximate approach we investigated these genes by quantitative real-time PCR (qPCR) analysis over the circadian cycle in torpid and normothermic animals at times of torpor entrance, mid torpor, arousal and post torpor. These qPCR data confirmed up regulation of dnah2, myo15a and vwf during torpor entrance, but a decreased mRNA level for all other investigated time points. This suggests that gene expression of structure genes as well as the procoagulation factor are specifically initiated during the early state of torpor and provides evidence for protective molecular adaptions in the hypothalamus of Djungarian hamsters including changes in structure, transport of biomolecules and coagulation.